Single-stage Modified Duhamel procedure for Hirschsprung's disease : Our experience - Paras R Kothari; Parag J Karkera; Abhaya R Gupta; Rahul Kumar Gupta; Gursev R Sandlas; Ritesh R Ranjan; Krushna K Kesan; Namrata Kothari (Wolters Kluwer Medknow Publications, 2012)
Introduction: Primary single-stage pull-through for Hirschsprung's disease (HD) has been reported to give comparable surgical outcomes to staged operations with less morbidity. Herein, we present our experience with single-stage Modified Duhamel procedure for management of HD. Patients and Methods: This was a review of 48 cases of HD who underwent single-stage Modified Duhamel procedure without a protective colostomy. Results: The age at surgery ranged from 6 months to 10 years (median - 9 months, mean - 2.3 years). The average weight of the child was 7.2 kg (range, 4.9-22 kg). 38 (79.2%) patients had classical rectosigmoid HD, the rest being long segment HD (the proximal most level being the splenic flexure). The average duration of surgery was 175 minutes (range, 130-245 minutes). The average blood loss was 45 ml. The average hospital stay was 7.2 days (range: 6-10 days). The major postoperative complications (n=3) included postoperative adhesive intestinal obstruction, anastomotic leak and persistent constipation due to residual aganglionosis. Each required a re-exploration. Minor complications included surgical site infection (n=3) and post-operative enterocolitis (n=3), which were managed conservatively. Six patients had constipation for a limited period post-operatively. All patients have a satisfactory functional outcome and normal development and growth. Conclusions: For HD, we recommend that single-stage Modified Duhamel procedure should be the preferred approach in view of its low morbidity, satisfactory functional outcome and avoidance of stoma, multiple surgeries and economic benefit in view of decreased hospital stay.